A case of esophageal cancer with an aberrant right subclavian artery treated with mediastinoscopic esophagectomy. Issue 2 (26th August 2020) - Hashimoto, Masashi; Shirakawa, Yasuhiro; Maeda, Naoaki; Tanabe, Shunsuke; Sakurama, Kazufumi; Noma, Kazuhiro; Fujiwara, Toshiyoshi
Abstract: An aberrant right subclavian artery (ARSA) is one of the famous anatomical abnormalities with a prevalence of 0.16–4.4%. In esophagectomy, anatomical abnormalities of the ARSA could cause complications with some surgical procedures. An 85‐year old man was referred to our department for esophageal adenocarcinoma that was at a slightly high position for esophagectomy with the abdominal approach. However, he had a significant past medical history. This risk factor made it difficult to perform thoracoscopic esophagectomy. He underwent mediastinoscopic esophagectomy (ME) with the left cervical and laparoscopic approach. The ARSA presented no difficulties with the ME surgical technique including the dissection of the left recurrent laryngeal nerve lymph node. Although this patient had a respiratory dysfunction and some difficulties in a prone position, ME enabled a safe esophagectomy with lymph node dissection.